Effects of the Pratt pouch model of dispensing nevirapine prophylaxis on HIV exposed infant completion of 6 weeks of prophylaxis in Uganda - Bitarakwate, Edward; Kim, Ashburn; Kazooba, Patrick; Khamasi, Ronald; Natumanya, Eliab; Herrera, Nicole; Owomugisha, Boaz; Robert, A. Malkin; Kisaakye, Linda (PLoS ONE, 2021)
The innovative Pratt pouch could optimize dispensing nevirapine prophylaxis to HIV-exposed infants in pre-measured single dose pouches to increase completion of the full 6 week infant nevirapine regimen. Materials and methods Nineteen health facilities with highest HIV positivity rates among pregnant women across 9 districts in southwest and central Uganda were assigned to control and intervention groups. HIV-positive women enrolled at intervention facilities received pouches filled with premeasured single doses of nevirapine using Uganda national guidelines, which were integrated into the existing drug distribution system. During antenatal care (ANC) women received 14 pouches to cover time until the 6 day postpartum visit, with an additional 8 pouches if women were delayed in returning to the facility, and 28 pouches after delivery. Women enrolled at control facilities received standard nevirapine syrup following delivery for postnatal infant prophylaxis. In a select number of intervention facilities, during ANC, women received all 42 pouches needed to complete the 6 weeks regimen. Medical record data from enrolled women were extracted; interviews with HIV-positive women during postnatal care visits were conducted. Data were collected January to August 2018 (control sites) and October 2019 to February 2020 (intervention sites). Unadjusted and adjusted logistic regression models were used to identify factors associated with facility delivery, postnatal care follow-up visit, and completion of the full 6 weeks infant nevirapine regimen. Results Significantly more women in the intervention (n = 320) versus control (n = 340) group had facility delivery (292/316, 92.4% versus 169/340, 49.7%, p<0.0001), postnatal visits within 2 weeks postpartum (295/297, 99.3% versus 133/340, 39.1%, p<0.0001) and reported their infants completing the full 6 weeks infant prophylaxis regimen (299/313, 95.5% versus 210/242, 86.8%, p = 0.0002). Dispensing 42 versus 14 pouches during ANC did not have negative effects on these outcomes. Among out-of-facility deliveries, a higher proportion of infants received nevirapine within 72 hours of birth in the intervention versus control group, 95.8% versus 77.9%. In multivariate models, the intervention group was the only significant factor associated with facility delivery or completion of the full 6 weeks infant prophylaxis.